Moving the Universities to the «Third Mission» in Europe, New Impulses and Challenges in Doctoral Education - Patrícia Santos (FahrenHouse, 2016)
In a society in which knowledge plays an increasing role, European universities have become essential actors. This has been reflected in demands to redefine their traditional missions and open the door to a «third mission». Links with external partners become a central part of its mission and priority of science policy and higher education. This set of trends is presented in this paper based on the analysis of one of the contemporary university components: the doctoral education. We have been seeing a renewed debate about the doctoral education that trigger changes in terms of their characteristics, functions and values. To this end, we developed a review of the scientific literature produced on the subject and the use of secondary sources regarding the development of scientific and educational systems in Europe. We also use the Portuguese case as an illustrative example of the analysis. We consider the agents operating in higher education within its borders and outside the sector, at global and national levels. What we see analyzing the doctoral education in Europe is the creation of new institutions, openness to more student groups, other teaching methods and more collaboration with industry. The development of doctoral programs is seen today to prepare researchers for careers in academia, but also for other sectors. Changes in the nature of research and knowledge produced by doctoral students, as in their own training paths, are important aspects.